Management and outcome of severely elevated blood pressure in primary care (Swiss Medical Weekly, 2012)
OBJECTIVE: In primary care the management of patients with acute severely elevated blood pressure (BP) is challenging. The aim of the study was to evaluate the initial management and outcome of patients presenting to their general practitioner (GP) with severe high blood pressure. METHODS: Twenty five general practitioners prospectively identified 164 patients presenting with severely elevated blood pressure (systolic BP >180 mm Hg and/or diastolic BP >110 mm Hg). At baseline, patients were categorised as having a hypertensive emergency, urgency or asymptomatic BP elevation. The therapeutic approach of the GPs was assessed and patient outcome at 12 month follow-up was analysed. RESULTS: Median age of 164 patents was 71 (range 22 to 97) years, 60 (37%) were male and 107 (65%) had pre-existing hypertension. Mean baseline systolic BP was 198 ± 16 (range 145 to 255) mm Hg, mean baseline diastolic BP was 101 ± 15 (range 60 to 130). In total, 99 (60%) of patients had asymptomatic BP elevation, 50 (31%) had hypertensive urgency, and 15 (9%) had a hypertensive emergency. Only around two thirds (61%) of patients were given immediate blood pressure lowering medication (most frequently calcium antagonists). Ten patients (6%) were immediately admitted to hospital. Systolic and diastolic BP declined significantly (p 110 mm Hg) to their GPs was asymptomatic, had pre-existing hypertension and was managed in GP’s office unless a hypertensive emergency was present. At three month follow-up mean systolic BP was still above target values.